STRATEGY TO DEVELOP ARABIC LANGUAGE CULTURE WITH BI’AH ARABIYYAH IN ISLAMIC BOARDING SCHOOL - Siti Imaniatul Muflihatin, Nurhasanah (Qouman : Jurnal Pendidikan dan Studi Islam, 2022)
One of the inhibiting factors in mastering a foreign language, including Arabic, is the low level of mastery obtained by students (pupils or santri). The most common causes found include an environment that is less nurturing (read: conducive) for students to be able to get used to using a foreign language in their daily lives. A nurturing environment is very much needed to encourage students to become independent learners. Therefore, institutions, namely Islamic boarding schools, which are religious educational institutions, need to develop a nurturing environment in fostering a love of Arabic actively and innovatively. This article aims to further explore the strategies that can be developed by Islamic boarding schools in fostering a love of Arabic by building an Arabic environment or what is often called Bi'ah Arabiyyah